Evolution of the Asian summer monsoon and regional karst ecological environment since the middle ages in Southwest China - Wang, Chen-Yi; Li, Jun-Yun; Chen, Chao-Jun; Zhang, Jian; Wu, Yao; Cheng, Hai; Shen, Chuan-Chou; Li, Ting-Yong (Scientific reports, 2025)
The frequent droughts and floods, closely associated with the Asian summer monsoon (ASM), has profoundly affected the ecological environment and economy in East Asia. While changes in the ASM are closely related to precipitation patterns, the specific mechanism still requires further investigation. This study utilized stalagmite records from the Feilong Cave in southwest China to reconstruct the evolution of the ASM since the Medieval Warm Period (MWP). The results indicated that the ASM strengthened during the MWP and weakened during the Little Ice Age (LIA), with changes in monsoon intensity primarily driven by solar activity and variations in tropical ocean-atmosphere circulation. Different phase combinations of the Atlantic Multidecadal Oscillation, and the Pacific Decadal Oscillation also influenced on the variations of the ASM. During the MWP, with warming of the northern hemisphere landmasses, the ASM intensified, enhancing the long-range transport of moisture from the southwest (Indian summer monsoon), leading to northward shifts of the rain belt in the eastern monsoon region in China and increased precipitation in northern China. Conversely, during the LIA, cooling of the northern hemisphere landmasses led to a weakening of the ASM and reduced southwest moisture transport, resulting in southward shifts of the rain belt in the eastern monsoon China and increased precipitation in southern China. Additionally, the abnormal southward shift of the Western Pacific Subtropical High led to prolonged retention of the rain belt in southern China, causing an increase in monsoonal rainfall in southern China. Comparison with monsoonal Chinese terrestrial proxy records reveals an antiphase relationship between northern and southern parts of the eastern China. During the MWP, the counterparts showed a “wet north-dry south” pattern, while during the LIA, a “wet south-dry north” pattern emerged. Furthermore, proxy records suggest that human activities exacerbated the deterioration of karst ecological environment in southwest China since the Middle Ages.
Gesehen am 20.08.2025